2009
DOI: 10.1002/ceat.200800619
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐Liquid Mass Transfer in Fibrous Bed Reactor with Counter‐Current Liquid Recycle

Abstract: In this work, the gas-liquid mass transfer in a lab-scale fibrous bed reactor with liquid recycle was studied. The volumetric gas-liquid mass transfer coefficient, k L a, is determined over a range of the superficial liquid velocity (0.0042-0.0126 m.s ), surface tension (35-72 mN/m), and viscosity (1-6 mPa.s). Increasing fluid velocities and viscosity, and decreasing interfacial tension, the volumetric oxygen transfer coefficient increased. In contrast to the case of co-current flow, the effect of gas superfic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Therefore, the K L a observed in the present study is comparable to that reported in other fibrous packed systems (Okada et al, 1996; Nikakhtari and Hill, 2005a; Kim and Deshusses, 2008; Martinov et al, 2009) and in STBs at similar mixing and aeration rate conditions (Chisti and Jauregui‐Haza, 2002; Puthli et al, 2004), suggesting that a fibrous bed packed ILALB may be expected to reach same cell densities as in well‐mixed bioreactors but with much limited costs.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Therefore, the K L a observed in the present study is comparable to that reported in other fibrous packed systems (Okada et al, 1996; Nikakhtari and Hill, 2005a; Kim and Deshusses, 2008; Martinov et al, 2009) and in STBs at similar mixing and aeration rate conditions (Chisti and Jauregui‐Haza, 2002; Puthli et al, 2004), suggesting that a fibrous bed packed ILALB may be expected to reach same cell densities as in well‐mixed bioreactors but with much limited costs.…”
Section: Resultssupporting
confidence: 91%
“…The increased K L a observed in Figure 11 must be due to increased interfacial area associated with variation of the coalescing gas fraction and the reduction in bubble size (Höller et al, 2001; Nikakhtari and Hill, 2005b; Martinov et al, 2009; Kilonzo et al, 2010). An additional increase in K L a is expected in the fibrous bed bioreactor system proposed in this study, due to enhanced K L value by increased number of localised turbulent eddies in the packing.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations